Triangular nanoperforation and band engineering of InGaAs quantum wells: a lithographic route toward Dirac cones in III–V semiconductors. (8th February 2019) - Post, L C; Xu, T; Franchina Vergel, N A; Tadjine, A; Lambert, Y; Vaurette, F; Yarekha, D; Desplanque, L; Stiévenard, D; Wallart, X; Grandidier, B; Delerue, C; et al.
Abstract: The design of two-dimensional periodic structures at the nanoscale has renewed attention for band structure engineering. Here, we investigate the nanoperforation of InGaAs quantum wells epitaxially grown on InP substrates using high-resolution e-beam lithography and highly plasma based dry etching. We report on the fabrication of a honeycomb structure with an effective lattice constant down to 23 nm by realising triangular antidot lattice with an ultimate periodicity of 40 nm in a 10 nm thick InGaAs quantum well on a p-type InP. The quality of the honeycomb structures is discussed in detail, and calculations show the possibility to measure Dirac physics in these type of samples. Based on the statistical analysis of the fluctuations in pore size and periodicity, calculations of the band structure are performed to assess the robustness of the Dirac cones with respect to distortions of the honeycomb lattice.